2022
DOI: 10.2147/copd.s380732
|View full text |Cite
|
Sign up to set email alerts
|

From COPD to Lung Cancer: Mechanisms Linking, Diagnosis, Treatment, and Prognosis

Abstract: Many studies have proved that the pathogenesis of the chronic obstructive pulmonary disease (COPD) and lung cancer is related, and may cause and affect each other to a certain extent. In fact, the change of chronic airway obstruction will continue to have an impact on the screening, treatment, and prognosis of lung cancer.In this comprehensive review, we outlined the links and heterogeneity between COPD and lung cancer and finds that factors such as gene expression and genetic susceptibility, epigenetics, smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 119 publications
0
21
1
Order By: Relevance
“…For example, chronic obstructive pulmonary disease (COPD) is a comorbidity of lung cancer and its pathogenesis is closely related to lung cancer. 4 Patients with COPD have a higher risk of developing lung cancer, which increases the incidence and mortality of lung cancer. 5 Studies have revealed that the mechanisms linking COPD and lung cancer may involve factors such as smoking, genetic susceptibility, epigenetics, epithelial-mesenchymal transition (EMT), chronic inflammation and oxidative stress damage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, chronic obstructive pulmonary disease (COPD) is a comorbidity of lung cancer and its pathogenesis is closely related to lung cancer. 4 Patients with COPD have a higher risk of developing lung cancer, which increases the incidence and mortality of lung cancer. 5 Studies have revealed that the mechanisms linking COPD and lung cancer may involve factors such as smoking, genetic susceptibility, epigenetics, epithelial-mesenchymal transition (EMT), chronic inflammation and oxidative stress damage.…”
Section: Introductionmentioning
confidence: 99%
“…5 Studies have revealed that the mechanisms linking COPD and lung cancer may involve factors such as smoking, genetic susceptibility, epigenetics, epithelial-mesenchymal transition (EMT), chronic inflammation and oxidative stress damage. 4,5 As a result, developing a COPD drug that also targets lung cancer is a current therapeutic goal. Additionally, people with idiopathic pulmonary fibrosis (IPF) develop lung cancer five times more often than the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-small cell lung cancer (NSCLC) accounts for approximately 80–85% of all lung cancer cases (Imyanitov et al ., 2021). Owing to the fact that lung cancer is often detected at an advanced stage (Lee and Kazerooni, 2022), even after receiving advanced treatments such as targeted therapy, chemoradiotherapy, and combination chemotherapy, the survival rates of patients are still unfavorable (Qi et al ., 2022). Therefore, it is essential to explore the possible prognostic biomarkers for lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer has the highest mortality rate among all tumors. Small‐cell lung cancer (SCLC) and non‐small cell lung cancer (NSCLC) are the two major subtypes, accounting for 15% and 85% of all lung cancers, respectively 1 . On average, about 2.2 million people are diagnosed with lung cancer every year, with 75% deaths 2 .…”
Section: Introductionmentioning
confidence: 99%